Conflict Management of Islamic Education Institusions in Indonesia: A Literature Review - Bashori, Bashori; Komariah, Nur; Nurlailisna, Novi; Habibi, Surya; Istikomah, Istikomah (FKIP Universitas Lampung, 2022)
The purpose of writing this article is to find out solutions in managing conflict in Indonesian Islamic education institutions. In particular, Islamic educational institutions in Islamic boarding schools and madrasas have a high probability of conflict compared to other educational institutions. This research is applying qualitative research through library research. The data obtained are compiled, analyzed, and concluded so as to obtain conclusions regarding the study of literature. The results of this study indicate that conflict management becomes very important in managing conflict in Islamic educational institutions as the development of quality educational institutions. In line with this, then what becomes our main concern in addressing conflict is that conflict cannot be avoided. Therefore, controlling conflict is a must in order to achieve goals in Islamic educational institutions in Indonesia. Conflict must be managed properly in order to create the goals of higher education institutions. In addition, conflict management is a solution to balance existing conflicts. Keywords: conflict management, islamic education institutions.DOI: http://dx.doi.org/10.23960/jpp.v12.i2.202208